p-Hydroxybenzoic acid synthesis in mycobacterium tuberculosis - Stadthagen, Gustavo; Kordula´kova, Jana; Griffin, R.; Constant, Patricia; Bottova, Iveta; Barilone, Nathalie; Gicquel, Brigitte; Daffé, Mamadou; Jackson, Mary (American Society for Biochemistry and Molecular Biology, 2005)
Glycosylated p-hydroxybenzoic acid methyl esters and structurally related phenolphthiocerol glycolipids are important virulence factors of Mycobacterium tuberculosis. Although both types of molecules are thought to be derived from p-hydroxybenzoic acid, the origin of this putative biosynthetic precursor in mycobacteria remained to be established. We describe the characterization of a transposon mutant of M. tuberculosis deficient in the production of all forms of p-hydroxybenzoic acid derivatives. The transposon was found to be inserted in Rv2949c, a gene located in the vicinity of the polyketide synthase gene pks15/1, involved in the elongation of p-hydroxybenzoate to phenolphthiocerol in phenolic glycolipidproducing strains. A recombinant form of the Rv2949c enzyme was produced in the fast-growing non-pathogenic Mycobacterium smegmatis and purified to near homogeneity. The recombinant enzyme catalyzed the removal of the pyruvyl moiety of chorismate to form p-hydroxybenzoate with an apparent Km value for chorismate of 19.7Mandakcatvalueof0.102s1. Strong inhibition of the reaction by p-hydroxybenzoate but not by pyruvate was observed. These results establish Rv2949c as a chorismate pyruvate-lyase responsible for the direct conversion of chorismate to p-hydroxybenzoate and identify Rv2949c as the sole enzymatic source of p-hydroxybenzoic acid in M. tuberculosis.